PENERAPAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - ali syamsuri; ika wahyu anita; heris hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This research aims to finding out and study the achievement and improvement off critical thinking skill off junior high school student with Problem Based Learning approach and using ordinary approach. The method used is an experimental method that involves two classes chosen at random selected classes i.e. VII A class using the Problem Baseed Learning and class VII B using a regular learning approach. The instrumen using is critical thingking skill. The results test analysis of postes data the value sig (2-tailed) is 0.002, while the test results of the difference of two average data gain, sig value (2-tailed) is 0.003. The findings in this studi were the achievement and improvement of the mathematical critical thinking skills of junior hiigh school students using the Problem Based Learning better than those using the usual approach